Effect of Dietary Inclusion of Graded Levels of Toasted Guar Meal (TGM) at Different Energy Efficiency on Egg Quality and Serum Parameters of White Leghorn Layers - Rao, M. Hanumanth; Rao, S.V. Rama; Gurram, Srinivas (Indian Journal of Animal Nutrition, 2019)
A biological trial was undertaken in a completely randomized design to study the effect of supplementation of toasted guar meal (TGM) at graded concentrations with two energy efficiencies of TGM on the performance and egg quality parameters of White Leghorn (WL) layers. A total of 224 layer chickens (Babcock, BV 300) were randomly distributed into 56 replicates with 4 birds per each colony cage in well ventilated platform 2 tier cage layer house. Seven experimental diets with graded levels of 0, 6, 12 and 18 % and two energy efficiency (50 % and 60 % of GE as ME) of TGM were prepared having similar concentrations of protein and ME. Each diet was fed ad libitum to 8 replicates from 27 to 42 weeks of age. The results showed that the egg quality (egg density, yolk index, yolk color, Haugh unit score, shell weight, shell percentage, shell thickness, shell strength) parameters and serum biochemical profile (albumin, protein and cholesterol) were not affected by incorporating TGM up to 18 % (180 g/kg diet) except albumen index which was significantly (P<0.05) higher at 18 % inclusion compared to other groups. From the results of the above study, it was concluded that TGM can be included in WL layer diets up to 18% without affecting Egg quality and serum parameters.